Risk-factors for stress-related absence among health care employees: a bio-psychosocial perspective. Associations between self-rated health, working conditions and biological stress hormones (Italian Journal of Public Health, 2006)
Background: Stress is a major cause of sickness absence and the health care sector appears to be especiallyat risk. This cross sectional study aimed to identify the risk factors for absence due to self-reported stressamong health care employees. Methods: 225 health care employees were categorized into two groupsbased on presence or not of self-rated sickness absence for stress. Questionnaire data and stress sensitivehormones measurements were used.Results: Employees with stress related sick leave experienced worse health, poorer work satisfaction as wellas worse social and home situations than those employees without stress-related sick leave. No-significantdifferences were identified regarding stress-sensitive hormones. The risk for employees, not satisfied atwork, of becoming absent due to stress was approximately three fold compared to those who reported beingsatisfied (OR 2.8, 95% confidence interval; (CI) 1.3 - 5.9). For those not satisfied with their social situation,the risk for sickness absence appeared to be somewhat higher (OR 3.2; CI 1.2 - 8.6).Individual factors such as recovery potential and meaning of life as well as work related factors such as skilldevelopment and work tempo predicted employee’ s work satisfaction.Conclusions: Based on cross sectional data, work-site and individual factors as well as social situationsappear to increase the risk for absence due to stress among health care employees. Lower recoverypotential, higher work tempo and poor leadership appeared to be related to the high degree of work relatedexhaustion experienced by employees.
Keywords: sickness absence; working conditions; stress hormones; health care employees